COMMUNICATION BETWEEN STAFF MEMBERS IN BASKETBALL TEAM: RULES, ROLES AND RESPONSIBILITIES - Jukic, Igor (Sport- és Egészségtudományi füzetek, 2025)
Good communication is the basis of interpersonal relations. This especially applies to relationships in top sport, top bas-ketball. However, good communication is the basis of good relationships between people in everyday life. In family, friendship, at work. High performance sport systems have their own structure and functional relationships. Usually, high performance staff consists of specialists of different profiles who have a unique task - to help the head coach in making the best decisions for the team and for the individuals in it.